2019
DOI: 10.3389/fendo.2019.00251
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenital Isolated Adrenocorticotropic Hormone Deficiency Caused by Two Novel Mutations in the TBX19 Gene

Abstract: Congenital isolated adrenocorticotropic hormone (ACTH) deficiency (CIAD) is a rare disorder which can result in 20% mortality in the neonatal period if misdiagnosed. A 2 years and 7 months old boy was hospitalized many times because of recurrent hypoglycemia. On initial physical examination, the patient showed special appearance and indications of fast growth (≥P97). Laboratory investigations revealed low levels of ACTH and cortisol in his plasma. Except thyroid-stimulating hormone, the anterior pituitary horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Alsaleem et al [20] Akcan et al [21] Unal et al [22] Abalı et al [12] Weijing et al [15] Our study had tall stature even though she had a low IGF1 level. They suggested that glucocorticoids inhibit IGFBP5.…”
Section: Some Features and Anthropometric Data Of Patients With The Tmentioning
confidence: 62%
See 2 more Smart Citations
“…Alsaleem et al [20] Akcan et al [21] Unal et al [22] Abalı et al [12] Weijing et al [15] Our study had tall stature even though she had a low IGF1 level. They suggested that glucocorticoids inhibit IGFBP5.…”
Section: Some Features and Anthropometric Data Of Patients With The Tmentioning
confidence: 62%
“…A lack of inhibition of IGFBP5 due to cortisol deficiency in IAD patients may have an underlying mechanism that promotes tall stature. Weijing et al [15] reported a similar growth pattern, but their patient had a normal IGF1 level; the tall stature was normalized after starting hydrocortisone. Similarly, our second patient was of tall stature with a normal IGF1 level; at follow-up once on treatment, her growth was within the normal range.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Heredity is autosomal recessive, with homozygous or compound heterozygous individuals expressing the disease. In a series of 91 patients with IAD, Couture et al described 21 different TBX19 mutations (4); however, new mutations have been identified since (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This disease is documented mostly in case reports or series. If pediatricians fail to recognize this disease in the neonatal period, it can result in 20-25% mortality (4,5).…”
Section: Discussionmentioning
confidence: 99%